The Government Social Services Policy on Central Europe-Indonesia for Refugee Protection: Are the Laws Sufficient for Refugee Protection in Both Countries? - Permatasari, Adinda Destaloka Putri (The Indonesian Journal of International Clinical Legal Education, 2021)
What is the refugee? a refugee is a person, or a group of people who have been forced to leaves his or her country because of the problem, such as like persecution, war or maybe violence that's happening in his/her country . A refugee has a well-founded fear of persecution that is happen in that country and some of the reasons are race or ethnic, religion, nationality, political opinion or maybe membership in a particular social group. And most of them can not return to they homeland and home because they are afraid to do so. War and ethnic, tribal and religious violence are leading causes of refugees fleeing their countries. Because of this case we should help them, and protect them. And In this paper we will talk about how does some country manage and treat the refugees in their country through the social services policy and law, and in this paper we will see from these two persepectives of countries, one from the Germany and Indonesia, we will find out, do the law and the policy in both of this country (Germany and Indonesia) are protect the refugee and how does the law and the policy that is rule the refugee well enough of its implementation in society.